Localisation of glycine receptors in the human forebrain, brainstem, and cervical spinal cord: an immunohistochemical review - Baer, Kristin; Waldvogel, Henry J.; Faull, Richard L.; Rees, Mark I. (Frontiers in Molecular Neuroscience, 2009)
Inhibitory neurotransmitter receptors for glycine (GlyR) are heteropentameric chloride ion channels that are comprised of four functional subunits, alpha1-3 and beta and that facilitate fast-response, inhibitory neurotransmission in the mammalian brain and spinal cord. We have investigated the distribution of GlyRs in the human forebrain, brainstem, and cervical spinal cord using immunohistochemistry at light and confocal laser scanning microscopy levels. This review will summarize the present knowledge on the GlyR distribution in the human brain using our established immunohistochemical techniques. The results of our immunohistochemical labeling studies demonstrated GlyR immunoreactivity (IR) throughout the human basal ganglia, substantia nigra, various pontine regions, rostral medulla oblongata and the cervical spinal cord present as intense and abundant punctate IR along the membranes of the neuronal soma and dendrites. This work is part of a systematic study of inhibitory neurotransmitter receptor distribution in the human CNS, and provides a basis for additional detailed physiological and pharmacological studies on the inter-relationship of GlyR, GABAAR and gephyrin in the human brain. This basic mapping exercise, we believe, will provide important baselines for the testing of future pharmacotherapies and drug regimes that modulate neuroinhibitory systems. These findings provide new information for understanding the complexity of glycinergic functions in the human brain, which will translate into the contribution of inhibitory mechanisms in paroxysmal disorders and neurodegenerative diseases such as Epilepsy, Huntington's and Parkinson’s Disease and Motor Neuron Disease.